Geysers valley CO 2 cycling geological engine (Kamchatka, Russia) - Kiryukhin, A; Sugrobov, V; Sonnenthal, E (Geofluids, 2018)
Copyright © 2018 A. Kiryukhin, et al. 1941-2017 period of the Valley of Geysers monitoring (Kamchatka, Kronotsky Reserve) reveals a very dynamic geyser behavior under natural state conditions: significant changes of IBE (interval between eruptions) and power of eruptions, chloride and other chemical components, and preeruption bottomtemperature.Nevertheless, the total deep thermal water discharge remains relatively stable; thus all of the changes are caused by redistribution of the thermal discharge due to giant landslide of June 3, 2007,mudflow of Jan. 3, 2014, and other events of geothermal caprock erosion and water injection into the geothermal reservoir. In some cases, water chemistry and isotope data point to localmeteoric water influx into the geothermal reservoir and geysers conduits. TOUGHREACT V.3 modeling of Velikan geyser chemical history confirms 20% dilution of deep recharge water and CO2 components after 2014. Temperature logging in geysers Velikan (1994, 2007, 2015, 2016, and 2017) and Bolshoy (2015, 2016, and 2017) conduits shows preeruption temperatures below boiling at corresponding hydrostatic pressure, whichmeans partial pressure of CO2 creates gas-lift upflow conditions in geyser conduits. Velikan geyser IBE history explained in terms of gradual CO2 recharge decline (1941-2013), followed by CO2 recharge significant dilution after the mudflow of Jan. 3, 2014, also reshaped geyser conduit and diminished its power.